Structured I/O streams in Clive: a toolbox approach for wide area network computing. Issue 1 (December 2017) - Ballesteros, Francisco
Abstract Most distributed applications and tools used in wide area networks and Cloud computing environments use the UNIX I/O framework. In this framework, processes use file descriptors for standard I/O and file access, with the traditionalopen /close /read /write interface. Although this design has proven to be excellent since the 1970s, it is not appropriate for today wide-area systems because of the implied RPCs and network latency. There are systems relying on message streams that perform well in such environments, but they depart from the toolbox approach embraced by UNIX, making it harder to combine existing programs to solve new tasks. In this paper we describe the design, implementation, and usage of a new I/O framework, built to enable the construction of services in environments with high latency, while preserving the programmability of the system as a whole and making it convenient to combine existing tools and programs. The framework relies on named channels for I/O. Each channel carries a stream of typed data including directory entries, raw bytes, and other application-specific data. Separate commands using the framework may be combined as in UNIX, but still tolerate high latencies as found in distributed and Cloud computing environments, enabling a toolbox approach in such environments.